Failure Analysis and Improvement of the Gearbox of Twenty-high Rolling Mill - Ye Naiwei; Lv Xiaobing; Deng Zhongxiang; Li Quanwei; Song Huijun; Wang Xuewu (Jixie chuandong)
The gearbox equipment failure analysis of a twenty-high cold rolling mill coiling machine is carried out.The stress analysis of gear is conducted,and the domestic design calculation and manufacture of gear is carried out,it is better meet the normal production of enterprise.